Re-storying SDG 14: life below water - Aaltonen, Heli (Nordic Journal of Art & Research, 2023)
In this text the focus is on re-telling multispecies stories about life below water, and the specific focus is on how to tell such stories, which awake moral agency in humans to care what happens with life below water. Sustainable development goal (SDG) number 14 Life below water concerns about “conserving and sustainable use the oceans, seas and marine resources for sustainable development”. To be able to achieve the goal there are created ten targets to create action for sustainable future. All ten targets are closely related with human use of life below water as a resource for own needs. What about thinking water as home for many living creatures and life below water as something we humans could have an empathic relationship with? The text suggests that the use of dramatic empathy in multispecies storytelling practice is close of the strategies of feministic care ethics where other-directedness and openness to difference may create empathic relationship with the other, which is essential for achieving attitude change and moral agency for more sustainable future.